Promotion of Meaning in Life and Wellbeing Among University Students During the COVID-19 Pandemic via a Service-Learning Subject - Zhu, Xiaoqin; Chai, Wenyu; Shek, Daniel T. L.; Lin, Li (Frontiers in Public Health, 2022)
Utilizing the principle of “learning by doing,” service-learning (SL) course provides a platform for university students to apply academic knowledge in serving the community, reflecting on the serving experiences, deepening their understanding of the knowledge, and further improving their competence, responsibility, well-being, and meaning in life (MIL). This study reported university students’ changes in psychological well-being (positive youth development attributes), subjective well-being (life satisfaction), and MIL after taking a SL subject during the COVID-19 pandemic through a one-group pretest-posttest design. Based on the data collected from 229 students (mean age = 20.86 ± 1.56 years, 48.0% females), repeated-measures multivariate general linear model (GLM) analyses revealed that students showed significant positive changes in well-being and MIL. In addition, pretest MIL scores positively predicted posttest scores of the two well-being measures but not vice versa. As predicted, improvement in MIL among students was closely associated with the positive changes in both psychological and subjective well-being measures. These findings suggest that SL participation during the pandemic may promote students’ life meaning and foster their well-being. Furthermore, MIL and well-being may improve simultaneously, and MIL enhancement may further contribute to improvement in psychological and subjective well-being. The findings further prove that SL is an effective pedagogy in higher education settings in promoting youth positive development.